Before Crisis Hits : Can Public Works Programs Increase Food Security? - World Bank (Washington, DC, 2014)
Fighting famine is basic to ending poverty and saving lives. Emergency aid, which arrives after the food has run out, isn't enough. Households most in need of emergency aid often don't have enough food during other times of the year, posing a broader challenge for devising programs that can cut hunger and build food security. Social protection programs, including grants, social assistance and public works programs are one way to transform people's lives and protect them both before and when disaster strikes. What works and under what circumstances is what policymakers and development experts want to know, especially those focused on famine breakouts in Africa and Asia. In 2003, the Ethiopian government partnered with donors and Non-Government Organizations (NGOs) to create a working coalition to improve food security for the poor. The result was the Productive Safety Net Program (PSNP), which went into effect in 2005. This program, the largest of its kind in Africa, initially targeted 7.6 million people (8 percent of Ethiopia's population) who suffered chronic food shortages and lived in areas prone to drought. Through a public works component and direct grants for those who can't work, the program aims to help households meet their food needs, keeping people fed and reducing the need to sell off productive assets. Ethiopian policymakers and international donors have long struggled with the challenge of reducing poverty amid weather shocks that disrupt harvests and threaten households with starvation. After years of emergency aid programs designed to provide short-term relief, both Ethiopia and donors wanted to create a program that could help people secure and build their lives, rather than just react to disaster. The result is Ethiopia's PSNP, which uses public works employment, social transfers and an agricultural asset-building program, to stabilize and strengthen poor households.